Workshop Penulisan Artikel Ilmiah sebagai Pengembangan Keprofesian Berkelanjutan Guru di Sekolah Menengah Atas - Imam Kusmaryono; Mochamad Abdul Basir (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service is carried out with the aim of improving the skills of writing scientific articles for teachers in the Kendal district, Central Java province. Strategy activities through workshops and assistance in writing scientific articles as a sustainable teacher professional development. The outputs of this workshop are (1) Teachers have good scientific article writing skills for teacher professional development, and (2) Teachers can produce scientific articles to be published in accredited national journals. The results of the workshop were effective in improving the skills of teachers in writing scientific articles where 70% of participants succeeded in compiling scientific articles